(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The study reveals research of ash content in different composite biomass fuels. It contains analysis of samples obtained from various local Latvian biomass types, i.e. reed, wood, hemp, flax shives and peat, by combining them in different proportions. Ash is a by-product derived from combustion process consisting mostly of inorganic substances that are left after a fuel is burnt. High level of ash content in a fuel is undesirable because it causes problems in automation of biomass combustion process. Previous studies carried out by the author show that average ash content in reeds is 2%, which is a high index comparing with wood where ash content is approximately 0,5-1%. Thus, the high ash content in reeds my cause problems in reed combustion in solid fuel boilers. Besides, it is not possible to ensure permanent reed collection that would ensure continuous reed fuel generating process all year long. In order to reduce the ash content to the optimal level and to diversify raw materials necessary for biomass fuel generating process, the author suggests using composite fuels by combining different biomass types. The study contains optimal combining proportions of different biomass types for composite fuel production basing on the ash content in them.